Composite metric R2 − R1ρ (1/T2 − 1/T1ρ) as a potential MR imaging biomarker associated with changes in pain after ACL reconstruction: A six‐month follow‐up. Issue 3 (16th September 2016) - Russell, Colin; Pedoia, Valentina; Majumdar, Sharmila; ,
ABSTRACT: This study looked to investigate a new quantitative metric, R 2 − R 1ρ (1/ T 2 − 1/ T 1ρ ), using magnetic resonance (MR) images and voxel‐based relaxometry (VBR) for detecting early cartilage degeneration and explore the association with patient‐reported outcomes measures (PROMs) in patients 6 months after ACL reconstruction. Sixty‐four patients from three sites were bilaterally scanned on a 3T MR with a combined T 1ρ / T 2 protocol to calculate R 1ρ (1/ T 1ρ ) and R 2 (1/ T 2 ) values at baseline and 6 months after reconstructive surgery. Non‐rigid registration was applied to align images onto a template, allowing VBR to determine VBR rate differences and explore cross‐sectional and longitudinal differences between injured and uninjured knees, generating Statistical Parametric Maps (SPMs). Baseline R 2 − R 1ρ differences were further correlated with change in PROMs from the Knee Injury and Osteoarthritis Outcome Score (KOOS) from baseline to 6 months. Cross‐sectional results demonstrated low relaxation rate differences in the injured patella (baseline: 21%, p = 0.01; 6‐months: 18%, p = 0.02), lateral tibia (baseline: 25%, p = 0.01; 6‐months: 24%, p = 0.01), and weight‐bearing regions of the tibia and femur. The uninjured patella showed significant longitudinal changes (17%, p = 0.02). R 2 − R 1ρ differences showed significant correlations with KOOS PROMs, particularly in the lateral tibia, patella, and trochlea. R 2 − R 1ρ difference VBR analyses provide new and highly sensitive parameters for assessing early cartilage degeneration in patients after ACL injury by integrating findings from both T 1ρ and T 2, commonly used relaxation time parameters, into a single metric. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 35:718–729, 2017.